The effects of age on clinical characteristics, hospitalization and mortality of patients with influenza‐related illness at a tertiary care centre in Malaysia - Wong, Pui Li; Sii, Hoe Leong; P'ng, Chun Keat; Ee, Soon Sean; Yong Oong, Xiang; Ng, Kim Tien; Hanafi, Nik Sherina; Tee, Kok Keng; Tan, Maw Pin (Wiley Open Access, 2020)
Background: Age is an established risk factor for poor outcomes in individuals with influenza-related illness, and data on its influence on clinical presentations and outcomes in the South-East Asian settings are scarce. The aim of this study was to determine the above among adults with influenza-related upper respiratory tract infection at a teaching hospital in Malaysia. Methods: A retrospective case-note analysis was conducted on a cohort of 3935 patients attending primary care at the University Malaya Medical Centre, Malaysia from February 2012 till May 2014 with URTI symptoms. Demographics, clinical characteristics, medical and vaccination history were obtained from electronic medical records, and mortality data from the National Registration Department. Comparisons were made between those aged <25, ≥25 to <65 and ≥65 years. Results: 470 (11.9%) had PCR-confirmed influenza virus infection. Six (1.3%) received prior influenza vaccination. Those aged ≥65 years were more likely to have ≥2 comorbidities (P <.001) and were less likely to present with fever (P =.004). One-third of those aged ≥65 years experienced hospitalization, intensive care admission or death within a year compared to 10% in the ≥25 to <65 years. Age ≥65 years was an independent predictor of hospitalization and death (OR = 9.97; 95% CI = 3.11-31.93) compared to those aged <25 years. Conclusion: Older patients in our cohort were more likely to have comorbidities and present with atypical features, with older age being an independent predictor of poor health outcomes. Our findings will now inform future health policies on older persons and economic modelling of adult vaccination programmes. © 2019 The Authors. Influenza and Other Respiratory Viruses Published by John Wiley & Sons Ltd.